(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Women over 30 require screening to improve HPV detection and Pap smear cytology. Only a negative Pap test and negative HPV test can confirm the absence of pathology.